KANDHORAK - Mudjijono Mudjijono (Jantra., 2018)
Eating, sleeping, and defecating (kandhorak) are a condition that the people of Gedongtengen district is trying to avoid. Sosrowijayan, Gandekan, Jlagran, and Badran are kampoongs located in Gedongtengen area. These kampoongs are stigmatized as “black areas” where fights, gambling, drinking liquor, and prostitution are there. A jaker which means security personnel is a favorite job for men. This profession is social capital for them. Using the perspective of Castill and Bordeu’s theory of habitus, this research looked at the phenomenon of jakers. The data were drawn from library research, in-depth observations, and interviews.The result of the research shows that people who are given a negative stigma could in turn make it to become a social capital for their economic activity.